Developing computer-based schedule delay analysis methods based on information flow analysis: a case study - Tsai, Ming-Kuan; Yang, Jyh-Bin; Yau, Nie-Jia (Journal of Civil Engineering and Management, 2013)
Schedule analysts often resolve diverse schedule delay problems in construction projects based on their subjective experiences. Although various process-based and mathematical-model schedule delay analysis methods are available for effective schedule delay analysis, these methods require time-consuming manual operation. The use of computer-based schedule delay analysis methods seems to be a solution. However, schedule analysts still have difficulty developing computer-based schedule delay analysis methods. Therefore, this study applies information flow analysis to classify the necessary work to develop computer-based schedule delay analysis methods. In contrast to numerous studies that focus only on computerizing a process-based or a mathematical-model schedule delay analysis method, this study constructs a computer-based method that integrates two process-based schedule delay analysis methods simultaneously. In a tested case study, the delay liability for the project owner and contractor was classified successfully. Importantly, this study provides a useful reference for similar applications in project management. First published online: 24 Oct 2013